SINERGI SEKOLAH DAN ORANG TUA DALAM PEMBATASAAN PENGGUNAAN GADGET PADA PEMBELAJARAN PAI DI SD TAHFIDZ QUR’AN NURUL IHSAN - Cholifah Cholifah (Universitas Muhammadiyah Tangerang, 2026)
ABSTRACT This study aims to find out the patterns of gadget use among students in their school and the impact of gadget use on students' concentration in learning PAI at Tahfidz Qur’an Nurul Ihsan Elementary School Kedungwaru Lor, Karanganyar District, Demak Regency. Gadgets have become communication tools that cannot be separated from human life. Gadgets not only used by adults but also by children. The widespread use of gadgets among children can hinder their learning process. The method used in this research is qualitative with a case study approach. Data was collected through observation, interviews, and documentation. The results of this study show that elementary school children use gadgets under strict supervision from parents at home, and the school prohibits students from bringing gadgets during the learning process. The use of gadgets doesn't directly disrupt focus during PAI lessons in class. However, exposure to gadgets and social media outside school hours can potentially affect students' concentration during learning. The school's efforts in managing study time, providing break programs, and involving parents have proven to be key factors in helping maintain students' focus. On the other hand, PAI teachers play an active role in giving advice and character reinforcement when they notice students starting to lose focus.